Catalog of New Varieties - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2023)
1. Campania, Cales. AE Unit, 7.75g, 22.5mm, c. 317 to 280 BC. Head of Apollo to left, wearing laurel wreath with leaves in opposing pairs, pentagram behind, CAΛENO before, dotted border / Acheloios Savo as a man-faced bull standing right on single line, lyre above, nothing below Acheloios, CAΛENO in ex. Taliercio- ; MSP -. Previously unknown without control mark beneath Acheloios. Artemide Kunstauktionen eLive 23, lot 15.